3x-2y=6
1) Add -3x to both sides.
3x−2y=6
+3x +3x
-----------------
−2y=−3x+6
2) Divide both sides by -2.
[tex] \frac{-2y}{-2} [/tex] = [tex] \frac{−3x+6}{-2} [/tex]
y=32x−3
3) Substitute the y with the equation
3x-2(32x-3)=6
3x-64x+6=6
4) Combine like terms
3x-64x+6=6
-61x+6=6
5) Subtract 6 from each side of the equation
-61x+6=6
-6 -6 (+6-5 gets crossed out)
--------------
-61x=0
6) Divide both sides by -61
[tex] \frac{-61x}{-61} = \frac{0}{-61} [/tex]
x=0
============================================================
Now that you've got you x intercept, use the x value and substitute it into the
y=32x−3
y=32(0)-3
y=0-3
y=-3
(0,-3)